Coaching in Complexity: Lessons Learned Investigating Implementation of Interventions in High Schools. (May 2022) - Kucharczyk, Suzanne; Szidon, Kate; Hall, Laura J.
High schools hold great potential as contexts within which educators implement evidence-based practices shown to change post-school outcomes for youth with autism spectrum disorder (ASD). Unfortunately, educators feel unprepared to use transition and disability-focused evidence-based practices. Coaching, as an essential feature of effective professional development, is an important process for supporting educators in their development of competencies for use of these practices. To inform the use of coaching in complex high school settings, the model used by the Center on Secondary Education for Students With ASD to implement a comprehensive package of disability- and transition-focused interventions in 30 schools is described and coaching data analyzed to offer lessons learned for developing professional development supports for secondary school practitioners. Limitations and implications for research and practice are discussed.